Damage effect of interleukin (IL)-23 on oxygen–glucose-deprived cells of the neurovascular unit via IL-23 receptor. (19th March 2015) - Wang, M.; Zhong, D.; Zheng, Y.; Li, H.; Chen, H.; Ma, S.; Sun, Y.; Yan, W.; Li, G.
Highlights: IL-23/IL-23R plays a critical role in cerebral ischemic injury. IL-23p19 shows no bioactivity to neurovascular cells for the lack of dimerization. IL-23 has a cytotoxic effect on oxygen–glucose-deprived neurovascular cells. The effect of IL-23 on neurovascular cells is IL-23R-expression-level dependent. Abstract: Interleukin-23/interleukin-23 receptor (IL-23/IL-23R) has been implicated in many inflammatory diseases. Previous research mainly focused on its ability to induce IL-17 production from T cells. However, few studies have investigated its role in cerebral ischemic injury. The aim of our study was to explore the potential effect of IL-23 on cells of the neurovascular unit (NVU) under an oxygen–glucose deprivation (OGD) condition and the role of IL-23R in IL-23-mediated effect. OGD of primary cells of the NVU and permanent middle cerebral artery occlusion (pMCAO) were used to produce experimental stroke in vitro and in vivo, respectively. IL-23 and IL-23R were detected by immunohistochemistry and western blot in pMCAO mice. Metabolic viability of cultured cells was assessed by MTT assay. The cell-associated proteins (Bcl-2, AQP4 and ET-1) were determined by western blot and enzyme-linked immunosorbent assay (ELISA). Immunofluorescence staining and western blot were used to detect the IL-23R expression. The results showed that the expression of IL-23/IL-23R was elevated in pMCAO mice. IL-23 could aggravate neuron damage, astrocyte swelling, and further impair the integrity of blood–brain barrier induced by OGD. In addition, the effect of IL-23 on cells of the NVU is mediated by IL-23R and is likely IL-23R-expression-level dependent. However, there are no such biological properties for the IL-23p19 subunit alone. Our study provides the first evidence that IL-23 has a toxic effect on cells of the NVU under OGD stress, which is mediated by IL-23R. These results not only help us better understand the role of IL-23/IL-23R in brain ischemia, but also provide a potential therapeutic target in stroke.